Preferential Adsorption of Heavy Metals on Activated Carbon - Bhole, V; Ramteke, DS (Bangladesh Journal of Scientific and Industrial Research, 2011)
The removal of heavy metals in single, two and three-component system through adsorption was studied and found instant removal at the initial concentration of the adsorbate. Adsorption of metals by activated carbon has been found to be dependent on pH, activated carbon dose and initial metal concentration, the type of activated carbon, its porosity and surface area. The Freundlich isotherms was used to fit the experimental data and to find out the adsorption parameters. The overall preferential adsorption pattern in multicomponent system of heavy metals was observed to be as cd> pb>cr. Generally in wastewater treatment system heavy metals are removed through adsorption in tertiary treatment. So this trend will be useful in removing maximum percentage of heavy metals preferably in multicomponent system. Key Words : Heavy metals; Adsorption; Single component system; Multicomponent system. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.2572 Bangladesh J. Sci. Ind. Res. 46(2), 211-218, 2011